Standard steroid treatment for autoimmune pancreatitis. Issue 11 (26th April 2009) - Kamisawa, T; Shimosegawa, T; Okazaki, K; Nishino, T; Watanabe, H; Kanno, A; Okumura, F; Nishikawa, T; Kobayashi, K; Ichiya, T; Takatori, H; Yamakita, K; et al.
Abstract : Objective: To establish an appropriate steroid treatment regimen for autoimmune pancreatitis (AIP). Methods: A retrospective survey of AIP treatment was conducted in 17 centres in Japan. The main outcome measures were rate of remission and relapse. Results: Of 563 patients with AIP, 459 (82%) received steroid treatment. The remission rate of steroid-treated AIP was 98%, which was significantly higher than that of patients without steroid treatment (74%, 77/104; p<0.001). Steroid treatment was given for obstructive jaundice (60%), abdominal pain (11%), associated extrapancreatic lesions except the biliary duct (11%), and diffuse enlargement of the pancreas (10%). There was no relationship between the period necessary to achieve remission and the initial dose (30 mg/day vs 40 mg/day) of prednisolone. Maintenance steroid treatment was given in 377 (82%) of 459 steroid-treated patients, and steroid treatment was stopped in 104 patients. The relapse rate of patients with AIP on maintenance treatment was 23% (63/273), which was significantly lower than that of patients who stopped maintenance treatment (34%, 35/104; p = 0.048). From the start of steroid treatment, 56% (55/99) relapsed within 1 year and 92% (91/99) relapsed within 3 years. Of the 89 relapsed patients, 83 (93%) received steroid re-treatment, and steroid re-treatment was effective in 97% of them. Conclusions: The major indication for steroid treatment in AIP is the presence of symptoms. An initial prednisolone dose of 0.6 mg/kg/day, is recommend, which is then reduced to a maintenance dose over a period of 3–6 months. Maintenance treatment with low-dose steroid reduces but dose not eliminate relapses.